A new method based on equivalent surfaces for simulation of the post-cooling in concrete arch dams during construction. (15th April 2020) - Conceição, José; Faria, Rui; Azenha, Miguel; Miranda, Manuel
Highlights: A new method is presented to simulate the effect of cooling pipes is concrete dams. Cooling coils are represented by a convective boundary. Each convective boundary is described by the Newton's cooling law. The method predicts well the temperatures in an arch dam monolith. It is 11 times faster than using a discrete representation of the cooling pipes. Abstract: In arch dams the thermal field has a crucial role on the structural behaviour. Throughout construction, the internal rise of temperature due to the heat released by cement hydration often results in significant volumetric deformations. When restrained either internally or externally, these deformations may lead to the development of considerable tensile stresses and, consequently, to the cracking of concrete. For this reason, establishment of temperature control measures is frequently deemed as necessary. One of the most relevant procedures is the circulation of water in embedded coils, which is also used to complete the cooling of concrete to the desired temperature for grouting the contraction joints. Despite its importance, detailed thermal analyses of arch dams during the construction phase are relatively scarce in literature, eventually because the existing methodologies based on the Finite Element Method (FEM), which represent the coils in a discrete way, require a huge computational effort. To overcome this drawback, the present paper proposes a new methodology to simulate the post-cooling effect, where the heat removal by the cooling coils is reproduced using fictitious convective boundaries. The framework to quantify the boundary coefficients is laid out, and comparisons are made in regard to analyses where explicit modelling of the cooling coils are performed. The proposed approach is also used to predict the thermal behaviour of a real arch dam monolith during construction, for which in-situ monitoring is available.